Development Strategy of Surowiti Hill Religious Tourism in Panceng Subdistrict, Gresik - Tisa Angelia; Eddy Imam Santoso (IJECA (International Journal of Education and Curriculum Application), 2018)
Religious tourism has spread to several areas in Gresik, East Java, and has potentially increased local revenue. Religious tourist objects include wali tourism and some other religious objects. Sunan Giri and Maulana Malik Ibrahim tourist sites are two religious objects frequently visited by many tourists and make the city of Gresik known as Wali Tourist City. Surowiti Hill site is one of the attractions in Gresik which consists of religious sites in the form of tombs and stopover Islamic religious leaders, as well as natural attraction in the form of caves. This research aims to determine the potential of Surowiti Hill Tourism and further formulate the development strategy as religious tourism. This research used exploratory method with SWOT analysis technique. The analysis reveals that the strengths and opportunities of the site lies on its natural destinations, such as Jamur Hill and Dalegan Beach, and the existence of religious sites already well known as Sunan Giri and Maulana Malik Ibrahim. The site’s weakness includes sanitary conditions, provision of clean water, and access to the destination. Threat factor includes the lack of support from community and government and the rapid development of other industries that might contaminate the nature. In sum, the development of Surowiti Hill site has not been optimal in terms of management and promotion.